Alumni in a relationship marketing perspective: the alumni-alma mater commitment relationship - Pedro, Ilda Maria Horta (2021)
Fostering relationships with alumni has consisted of framing strategies to increase competitiveness amongst higher education institutions (HEIs) in Europe and particularly in Portugal. This thesis aims to understand the alumni-alma mater commitment relationship, through the identification of its drivers, indicators, and alumni patterns leading to an intention to commit. The work was developed at the University of Algarve (UAlg) through qualitative and quantitative research methods. Results are embodied in three papers. The first study draws upon alumni opinions regarding four main dimensions: academic experience, current situation, commitment indicators and the HEI’s commitment. The information was obtained through three focus groups (paper one). A structural equation modelling approach was used to investigate the relationship between a set of latent variables, identified in the qualitative research and supported by the literature, and the commitment relationship. To this end, a sample of 2,008 alumni was obtained through an online survey (paper two). The obtained results helped in the development of the last phase of the work, in which was applied a cluster analysis to segment the alumni and a binomial regression model to identify determinants of the intention to collaborate (paper three). The results show that the affective, cognitive and HEI’s commitment directly influence the commitment relationship. Alumni stress their intention to recommend, share their experience with current students, and give their help when it is necessary as ways to give back. Furthermore, they also recognise the importance of benefits and advantages in this relationship. Five segments of alumni were identified through clustering analysis, revealing valuable information for decision-making, particularly regarding an expressed willingness to participate in fundraising campaigns, which is relevant in a context where these campaigns are not very common. Results of the regression model showed that predictors of intention to collaborate comprised participation in extracurricular activities, sense of belonging, and elements considered in HEI’s commitment (solicitation, communication, and quality). HEI’s responsibility is underlined as a true catalyst in the commitment relationship process. The general conclusions of this thesis are in line with the literature, but they also add value in the context of European higher education, particularly in Portugal, where the alumni culture is starting to make small steps.